Paediatric transoral robotic-assisted adenotonsillectomy: a new anaesthetic experience in Malaysia / Zawiah Kassim … [et al.] - Kassim, Zawiah; Ahmad, Fauziah; Mustapha Kamar, Rusnaini; Misiran, Karis (Universiti Teknologi MARA Cawangan Selangor, 2019)
Safety and feasibility of transoral robotic surgery (TORS) in adults for otolaryngology surgery, mainly in the treatment of oropharyngeal carcinoma and obstructive sleep apnoea has already been established several years ago. However, less is known with respect to the role and safety of TORS for otolaryngology surgery in the paediatric age group and its description in the literature is currently insufficient. As paediatric patients are unique in their anatomy, physiology and pharmacological kinetic, special attention and consideration has to be applied when using TORS, hence this increases the perioperative challenges. Herewith we present our experience in anaesthetising a paediatric patient for TORS adenotonsillectomy which is the first not only in our centre but in Malaysia. Our major obstacle was the limited airway access as the area of concern was shared by the anaesthesiologist, surgeon and also the robotic system. Haemodynamic stabilisation was a challenge compared to the conventional method as the operative time increased due to robot docking time and the new surgical learning process. In our opinion, the key point for the success of TORS adenotonsillectomy in paediatric patients is good communication and teamwork between all personnel involved in the surgery.